HUBUNGAN POLA KONSUMSI JAJANAN DAN BESAR UANG SAKU DENGAN STATUS GIZI ANAK UPT SPF SDN 101898 LUBUK PAKAM - Nasution, Erlina; Ratna Zahara; Yati (Poltekkes Kemenkes Medan, 2025)
Nutritional problems in elementary school children that occur today are still quite high where these nutritional problems can affect the Nutritional Status of elementary school children. This is caused by several factors directly, namely Snack Consumption Patterns and indirectly, namely the Amount of Pocket Money. Snack intake at school affects the provision of Pocket Money. Unhealthy Snack Consumption Patterns are considered less good and can interfere with the eating patterns of elementary school children. The purpose of this study was to determine the correlation Between Snack Consumption Patterns and the Amount of Pocket Money with the Nutritional Status of Children at SPF SDN 101898 Lubuk Pakam.This study was conducted at SPF SDN 101898 Lubuk Pakam School. Research Time and Data Collection will be carried out in early October 2023 to August 2024. The type of research used was observational with a Cross Sectional design. The population used as a sample for this study were all students in grades VA and VB at SPF SDN 101898 Lubuk Pakam, totaling 47 students. The results of the study based on the correlation between snack consumption patterns and nutritional status obtained a p value = 0.018 (p <0.05) meaning Ha was accepted, while the Correlation between the Amount of Pocket Money and Nutritional Status obtained a p value = 0.045 (p <0.05) meaning Ha was accepted. From these results and discussions, it can be concluded that there is a Correlation between Snack Consumption Patterns and the Nutritional Status of Children at SPF SDN 101898 Lubuk Pakam and there is a correlation between the Amount of Pocket Money and the Nutritional Status of Children at SPF SDN 101898 Lubuk Pakam.